The Risk Factors of Nonalcoholic Fatty Liver Disease in Morbidly Obese Patients Undergoing Bariatric Surgery in Iran - Ladan Aghakhani; Neda Haghighat; Masoud Amini; Seyed Vahid Hosseini; Seyed Jalil Masoumi (Gastroenterology Research and Practice)
Background and Aims. Nonalcoholic fatty liver disease (NAFLD) is common in severely obese individuals undergoing bariatric surgery. Assessing the prevalence and severity of NAFLD seems crucial since it may affect the prevention or development of more severe forms of fatty liver. Methods. This cross-sectional study was conducted on 228 severely obese individuals undergoing bariatric surgery. Abdominal ultrasonography was done, and clinical and biochemical factors (liver enzymes, lipid profile, and fasting blood sugar (FBS)) were assessed. Results. The mean body mass index (BMI) was 43.45±5.92 kg/m2. The prevalence of NAFLD was 49.12% (mild steatosis: 37.5%, moderate steatosis: 36.6%, and severe steatosis: 25.8%). The main risk factors of NAFLD were weight (p=0.002), BMI (p=0.003), alanine aminotransferase (ALT) (p<0.001), aspartate aminotransferase (AST) (p<0.001), serum triglycerides (TGs) (p=0.004), and FBS (p=0.039). The results revealed a statistically significant decrease in the mean level of high-density lipoprotein cholesterol (HDL-C) (p=0.044). However, no significant association was found between the severity of liver steatosis and the presence of comorbidities such as hypertension, diabetes, hypothyroidism, and dyslipidemia. Conclusions. More severe NAFLD was associated with increased weight and BMI. Elevated ALT, AST, TG, and FBS levels and decreased HDL-C levels were also the risk factors of NAFLD and its progress to more severe conditions.